Sistem Informasi Inventarisasi Sarana dan Prasarana Sekolah Berbasis Website pada SMPN 292 Jakarta Barat - Asep Sumantri; Niken Harsanti; Aprilianti Putri; Ghessa Nur Azizah; M. Fathan Arbiansyah (CV. ALIM'SPUBLISHING, 2026)
Inventory management of school facilities and infrastructure is an important activity in supporting effective and efficient asset administration. SMPN 292 West Jakarta still manages inventory data manually, resulting in difficulties in recording, searching, monitoring assets, and generating inventory reports. This study aims to design and develop a web-based School Facilities and Infrastructure Inventory Information System to support integrated asset management. The research employed the Research and Development (R&D) method consisting of problem identification, literature review, data collection, requirements analysis, system design, implementation, and system testing. The system was designed using Unified Modeling Language (UML) and Entity Relationship Diagram (ERD), while system testing was conducted using the Black Box Testing method. The developed system provides features for managing inventory data, storage locations, acquisition sources, user management, and inventory reporting. The results indicate that the developed information system improves the efficiency, accuracy, and effectiveness of inventory management compared to manual procedures. Furthermore, the Black Box Testing results show that all system functionalities operate according to user requirements. Therefore, the proposed system is considered suitable for supporting facilities and infrastructure management at SMPN 292 West Jakarta.